808 Changing nature of major trauma from 2000 to 2019 in England and Wales: observational registry study. Issue 3 (21st February 2022) - Shanahan, Thomas; Tomkins, Michael; Bouamra, Omar; Edwards, Antoinette; Kumar, Dhushy Surendra; Coats, Timothy; Lecky, Fiona
Abstract : Aims/Objectives/Background: Low energy transfer mechanisms – predominately falls from a standing height – have been identified as the most prevalent cause of major trauma in higher-income countries. This study examines the epidemiological trends in major trauma in England and Wales between 2000 – 2019, incorporating changes in mechanism of injury, imaging practices, case ascertainment and national demographic shifts. In addition, changes in the whole cohort of major trauma patients and differences between patients who suffered high energy and low energy mechanism of injury are described. Methods/Design: A retrospective observational cohort study was conducted using Trauma Audit and Research Network (TARN) data. Patients with an injury severity score (ISS) >15 admitted to hospital in England and Wales between 1 January 2000 to 31 December 2019 were included. The primary outcome was the temporal trend in the proportion of major trauma sustained through low energy transfer, and its association with imaging practices, case ascertainment and demographic changes. Results/Conclusions: 241, 484 participants were included in the analysis, of which 96, 833 were classified as low energy. Low energy trauma accounted for 12.5% in 2000 (n = 373), rising to 52.6% (n=16, 087) in 2019. Over the same period the proportion of patients receiving CT imaging increased from 20.7% (n=676) to 88.9% (n=27, 174). TARN hospital membership doubled from 96 to 179 hospitals, and the annual mean numbers of cases per hospital per annum increased sixfold from 31 to 174. Case ascertainment improved from 42% in 2008 to 95% in 2019. Significant differences were observed in the demographics, injury patterns, presenting physiology, care pathways, and outcomes between the high and low energy cohorts. Changes in imaging and reporting practices have revealed a previously hidden burden of injury resulting from low energy transfer mechanisms. It is essential that future research recognises this distinct cohort and investigates how trauma systems can be changed to optimise outcomes.